(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE "HUMAN RESOURCES AND MODERN PROFESSIONS IN THE WORLD" – Aachen, Germany, 2024)
Achieving a hemostatic effect by physical methods of influencing the wound surface and the parenchyma’s bleeding vessels is rational mainly for its shallow and superficial injuries. To stop bleeding from parenchyma vessels with a diameter of more than 1.0 mm, an increase in exposure and power of energy exposure is required, which inevitably leads to damage to the stromal elements of the organ and increases the area of parenchyma necrosis to a depth of 4-8 mm, and the resulting coagulation eschar often serves as a substrate for infection and recurrence of bleeding. Physical methods of hemostasis during operations on parenchymal organs do not meet the requirements of the "ideal method", which should be accompanied by minimal blood loss or its absence, minimal parenchymal necrosis, and reduced operation time. In regard with this, the development of fastacting, safe, effective and economical hemostatic materials is of great clinical and social importance.